Multi-stage assembly material based on azobenzene liquid crystal block copolymer, preparation method of multi-stage assembly material and resin reinforcing and toughening method
By blending the multi-stage assembly material of azobenzene liquid crystal block copolymer with the resin matrix, the problems of complex process and lack of multi-level assembly in the prior art are solved, and efficient toughening of the resin-based material is achieved, which significantly improves the Its strength and toughness.
Patent Information
- Application Number
- CN202411406192.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2024-12-20
AI Technical Summary
In the prior art, the toughening process of resin-based materials is complex and lacks fine multi-level assembly, resulting in low toughening efficiency.
Azobenzene liquid crystal block copolymer is used to prepare multi-stage assembly materials through polymerization and annealing, and blend it with a resin matrix to improve the strength and toughness of the resin.
The resin toughening process is simplified, and multi-level assembly such as multi-layer blades, single-layer blades, multi-layer squares are formed, which significantly improves the tensile toughness and fracture strength of the resin, and the toughening effect can reach 5.2 times that of ordinary resin films.
Smart Images

Figure CN119161549A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of resin-based material modification, and specifically to a multi-stage assembly material based on azobenzene liquid crystal block copolymers, a preparation method thereof, and a method for strengthening and toughening resins. Background Art
[0002] Solution self-assembly of block polymers is a convenient method to construct assemblies with different morphologies and sizes. By adjusting the structure and assembly conditions of block polymers, researchers have constructed assemblies with rich morphologies in solution, such as one-dimensional nanowires, strips, rods, and tubes, two-dimensional sheet assemblies, and three-dimensional flower-like assemblies. Assemblies can be used in catalysis, biomedicine, nanocomposites, and optical devices. Among them, two-dimensional and three-dimensional multi-level assemblies have broader application prospects based on their unique regular multi-level structures and functions.
[0003] At present, the resin-based materials required in the industrial field often need to have both high strength and high toughness mechanical properties. Thermosetting resins, such as epoxy resins EPs, have excellent mechanical properties, chemical stability, heat resistance and corrosion resistance, but the lack of toughness limits their application. The toughening methods of EPs can be divided into homogeneous toughening systems and heterogeneous toughening systems. The homogeneous toughening system achieves the increase of system toughness by uniformly dispersing the modifier into the epoxy resin matrix to form an interpenetrating network without phase separation; while the heterogeneous system uses the phase separation between the modifier and the resin matrix to achieve the toughening of the resin. The toughening modification methods of thermoplastic resins are similar to those of thermosetting resins.
[0004] With the help of self-assembly, the mechanical properties of thermosetting resins or thermoplastic resins can be better improved. For example, phosphorus-modified polyhedral oligomeric silsesquioxane (P-POSS) and polyethyleneimine are self-assembled in aqueous solution to obtain PPI assemblies with ionic bonds and rigid structures. PPI and cured EPs can form a heterogeneous toughening system, thereby improving the fracture toughness of EPs. For thermoplastic resins, for example, with the help of the synergistic self-assembly effect of nanoelastic fibers and sebacic acid diphenylhydrazide, the crystal morphology and phase structure of polylactic acid resin can be controlled by in-situ fiberization, and the sea island structure of polylactic acid resin material can be transformed into an incomplete bicontinuous structure, thereby improving the toughness of polylactic acid resin without losing the stiffness of polylactic acid resin. In addition, cylindrical micelles based on liquid crystal block copolymers can be prepared in solution through an in-situ self-assembly process driven by the liquid crystal ordering effect. Such cylindrical micelles can be used as additives to toughen polymethyl methacrylate matrices.
[0005] However, there are still many shortcomings in the use of self-assembly methods to strengthen and toughen resin matrices: (1) The assembly structures used are mostly simple one-dimensional or two-dimensional structures, and there is a lack of sophisticated multi-level assemblies and methods for strengthening and toughening resins; (2) The resin strengthening and toughening process is relatively cumbersome and complex. For example, some inorganic modifiers also require special surface modification, which greatly reduces the efficiency of strengthening and toughening. Summary of the invention
[0006] The present application provides a multi-level assembly material based on azobenzene liquid crystal block copolymers and a preparation method thereof, as well as a method for strengthening and toughening resins, aiming to solve the problems of complex strengthening and toughening processes and lack of fine multi-level assemblies in the prior art.
[0007] In order to achieve the above objectives, the present application adopts the following technical solutions.
[0008] In a first aspect of the present application, a method for preparing a multi-stage assembly material based on an azobenzene liquid crystal block copolymer is provided, comprising:
[0009] S1, polymerizing azobenzene methyl acrylate monomer and a chain transfer agent in a first solvent under an inert atmosphere under the action of an initiator to obtain a liquid crystal block copolymer;
[0010] S2, annealing the liquid crystal block copolymer in a second solvent to obtain a multi-level assembly material.
[0011] Preferably, the chemical structure of the azobenzene methyl acrylate monomer is as shown in formula (I):
[0012]
[0013] Wherein, x is an integer from 2 to 12; R 1 Any one selected from methyl, ethyl, propyl, n-butyl, n-pentyl or methoxy.
[0014] Preferably, the chemical structure of the chain transfer agent includes any one of the following:
[0015]
[0016] Wherein, n is an integer of 20 to 200; m is an integer of 10 to 200.
[0017] Preferably, the first solvent includes any one of tetrahydrofuran, dioxane, N,N-dimethylformamide or toluene;
[0018] The polymerization reaction temperature is 60 to 90° C., and the reaction time is 12 to 72 hours.
[0019] Preferably, the second solvent is a poor solvent for the liquid crystal block copolymer or a mixed solvent of a poor solvent for the liquid crystal block copolymer and a good solvent;
[0020] The poor solvent includes at least one of methanol, ethanol, isopropanol, n-butanol or deionized water;
[0021] The good solvent includes at least one of N,N-dimethylformamide, dimethyl sulfoxide, tetrahydrofuran, dichloromethane or N-methylpyrrolidone;
[0022] The volume ratio of good solvent to poor solvent in the mixed solvent is (0.01-0.03):1.
[0023] Preferably, the annealing treatment temperature is 50° C. to 120° C., and the insulation time is 0.5 to 24 hours.
[0024] Preferably, the molar ratio of the azobenzene methyl acrylate monomer, the initiator and the chain transfer agent is (30-2000):1:(3-10);
[0025] The initiator is azobisisobutyronitrile.
[0026] In a second aspect of the present application, a multi-stage assembly material prepared by the above preparation method is provided.
[0027] The third aspect of the present application provides a method for strengthening and toughening a resin, comprising:
[0028] The organic resin matrix solution and the solution of the multi-stage assembly material are mixed evenly, added into a mold and allowed to stand, and then kept at 20 to 40° C. for 1 to 30 hours;
[0029] The mass of the dispersion of the multi-stage assembly material accounts for 0.1-10 wt % of the mass of the organic resin matrix.
[0030] Preferably, the organic resin matrix solution is prepared by dissolving the organic resin matrix in water, glycerol or ethanol, and the concentration thereof is 0.5 to 3 g / mL;
[0031] The organic resin matrix is at least one of epoxy resin, polyurethane resin, phenolic resin or polyvinyl alcohol resin.
[0032] Compared with the prior art, the beneficial effects of this application are:
[0033] The present application obtains an azobenzene liquid crystal block polymer with liquid crystal order by polymerizing an azobenzene methyl acrylate monomer with a reversible addition-fragmentation chain transfer polymerization monomer; the block polymer is thermally annealed in a specific solvent to achieve regulation of the morphology of the polymer assembly to form multi-level assemblies such as multi-layer blades, single-layer blades, multi-layer square sheets, and single-layer square sheets.
[0034] The block copolymer and multi-level assembly of the present application are easy to obtain. The multi-level assembly of different morphologies is added to the common resin matrix as a reinforcing and toughening agent in a blending manner. The strength and toughness of the common resin matrix can be increased by simple blending, which greatly simplifies the strengthening and toughening process of the resin. The multi-level assembly of different morphologies of the present application contributes to the strengthening and toughening of the resin matrix. The tensile toughness of the composite film can be increased to 5.2 times that of the common resin film, and the fracture strength is also greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0036] Figure 1 The hydrogen nuclear magnetic resonance spectrum of the linker transfer agent prepared in this application;
[0037] Figure 2 The hydrogen nuclear magnetic resonance spectrum of the azobenzene methyl acrylate monomer prepared in this application;
[0038] Figure 3 The hydrogen nuclear magnetic resonance spectrum of the azobenzene block polymer prepared in this application;
[0039] Figure 4 TEM images of multi-level assembly materials BCP-1, BCP-2, and BCP-3;
[0040] Figure 5 TEM image of the multi-level assembly material BCP-4;
[0041] Figure 6 The stress-strain curves of toughened and reinforced polyvinyl alcohol composite film and ordinary polyvinyl alcohol composite film. DETAILED DESCRIPTION
[0042] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0043] In the following description of this embodiment, the terms "include", "comprising", "having" and "containing" are all open terms, meaning including but not limited to.
[0044] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.
[0045] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0046] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0047] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0048] Those skilled in the art will appreciate that the numerical ranges in the embodiments of the present application are to be construed as specifically disclosing each intermediate value between the upper and lower limits of the scope. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present application. The upper and lower limits of these smaller ranges may be independently included or excluded in the scope.
[0049] Unless otherwise specified, the technical / scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which this application belongs. Although this application only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of this application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0050] In a first aspect, the present application provides a method for preparing a multi-stage assembly material based on azobenzene liquid crystal block copolymer, comprising:
[0051] S1, azobenzene methyl acrylate monomer and chain transfer agent are polymerized in a reaction solvent under an inert atmosphere under the action of an initiator to obtain a liquid crystal block copolymer;
[0052] In the present application, an azobenzene liquid crystal block polymer with liquid crystal order is obtained by polymerizing an azobenzene methyl acrylate monomer with a reversible addition-fragmentation chain transfer polymerization monomer, and its chemical structure is shown in formula (I):
[0053]
[0054] Wherein, x is an integer from 2 to 12; R 1 Any one selected from methyl, ethyl, propyl, n-butyl, n-pentyl or methoxy.
[0055] In the present application, the chemical structure of the chain transfer agent includes any one of the following:
[0056]
[0057] Wherein, n is an integer of 20 to 200; m is an integer of 10 to 200.
[0058] In the present application, a liquid crystal block copolymer is obtained by polymerizing azobenzene methyl acrylate monomer and a chain transfer agent in a first solvent, wherein the molar ratio of azobenzene methyl acrylate monomer, initiator and chain transfer agent is (30-2000):1:(3-10); the polymerization temperature is 60-90°C, and the reaction time is 12-72 hours. Specifically, the first solvent includes any one of tetrahydrofuran, dioxane, N,N-dimethylformamide or toluene. The initiator is preferably azobisisobutyronitrile.
[0059] The chemical structure of the liquid crystal block copolymer is shown in formula (II):
[0060]
[0061] In formula (II), R 1 Any one selected from methyl, ethyl, propyl, n-butyl, n-pentyl, and methoxy;
[0062] R 2 Selected from
[0063] x is an integer from 2 to 12; n is an integer from 20 to 200.
[0064] S2, annealing the liquid crystal block copolymer in a second solvent to obtain a multi-level assembly material.
[0065] In the present application, the second solvent can be selected from a poor solvent of the liquid crystal block copolymer alone, or a mixed solvent of a good solvent of the liquid crystal block copolymer and a poor solvent. Among them, the poor solvent includes at least one of methanol, ethanol, isopropanol, n-butanol or deionized water; the good solvent includes at least one of N,N-dimethylformamide, dimethyl sulfoxide, tetrahydrofuran, dichloromethane or N-methylpyrrolidone. The volume ratio of the good solvent to the poor solvent in the mixed solvent is (0.01-0.03):1.
[0066] In the present application, the liquid crystal block copolymer is dispersed in a second solvent, heated to 50° C. to 120° C., kept warm for 0.5 to 24 hours, and annealed to obtain a dispersion of the multi-stage assembly material.
[0067] The present application obtains azobenzene liquid crystal block polymers with liquid crystal order by polymerizing azobenzene methyl acrylate monomers with reversible addition-fragmentation chain transfer polymerization monomers; the block polymers are subjected to thermal annealing in a specific mixed solvent to achieve regulation of the morphology of the polymer assembly, and obtain a multi-level assembly with morphological structures such as multi-layer blades, single-layer blades, multi-layer square pieces or single-layer square pieces. The multi-level assembly material prepared in the present application is a three-dimensional structure, which has a better strengthening and toughening effect on the resin matrix.
[0068] The present application also provides a method for strengthening and toughening a resin, comprising:
[0069] The organic resin matrix solution is mixed evenly with the dispersion of the multi-stage assembly material, added to a mold and allowed to stand, and then kept at 20 to 40° C. for 1 to 30 hours to evaporate the solvent, thereby obtaining a reinforced and toughened organic resin, wherein the mass of the dispersion of the multi-stage assembly material accounts for 0.1 to 10 wt % of the mass of the organic resin matrix.
[0070] In the present application, the organic resin matrix solution is prepared by dissolving the organic resin matrix in water, glycerol or ethanol, and the concentration thereof is 0.5 to 3 g / mL; the organic resin matrix can be selected from at least one of epoxy resin, polyurethane resin, phenolic resin or polyvinyl alcohol resin.
[0071] The present application is further described below by way of examples.
[0072] Example A macromolecular chain transfer agent containing polyethylene glycol was prepared, and its synthesis route was as follows:
[0073]
[0074] 5.00 mmol of polyethylene glycol monomethyl ether (PEG-OH, number average molecular weight is about 2000 g·mol -1 ), 19.4mmol of N,N'-dicyclohexylcarbodiimide (DCC), 1.00mmol of 4-dimethylaminopyridine (DMAP) and 5.48mmol of 2-(dodecylthiothiocarbonylthio)-2-methylpropionic acid (DMA) were dissolved in 50.0mL of dichloromethane, stirred at 0°C for 20min under nitrogen and reacted at room temperature for 24h. After the reaction, the dichloromethane was removed by rotary evaporation, and the remaining solution was precipitated in ice ether three times, and the precipitate was dried in a vacuum oven for 24h to obtain a light yellow powder, i.e., a macromolecular chain transfer agent, recorded as PEG 45 -DMA, its nuclear magnetic resonance hydrogen spectrum is characterized as Figure 1 shown.
[0075] Example Azobenzene methyl acrylate monomer was prepared, and the synthesis route was as follows:
[0076]
[0077] Weigh 0.20 mol of 4-n-butylaniline and add it to a three-necked flask containing 250 mL of 3M hydrochloric acid; weigh 0.21 mol of NaNO 2 Dissolve in 75 mL of deionized water and heat NaNO 2 The aqueous solution was slowly added dropwise to a three-necked flask, and the reaction was rapidly stirred in an ice-water bath for 1 hour to obtain a dark brown solution. 200 mL of a 10% NaOH aqueous solution was taken, 0.21 mol of phenol was added thereto and stirred to dissolve to prepare a solution, and the dark brown solution was added dropwise to the solution in an ice-water bath, and continued to stir for 2 hours after the addition was completed, and then the ice-water bath was removed to return to room temperature, and the reaction solution was adjusted to weak alkalinity with a hydrochloric acid aqueous solution, filtered, washed with water until neutral, and the solid was placed in a 30°C vacuum oven to dry to obtain 42.1 g of 4-(4-butylphenylazo)phenol, with a yield of 81%.
[0078] In a 1000 mL three-necked flask, 0.10 mol of 4-(4-butylphenylazo)phenol, 0.74 mol of 1,6-dibromohexane, and 0.76 mol of K 2 CO 3 and 500mL acetone, heated in an oil bath at 70℃ for reflux reaction for 24h. After the reaction, filter while hot, wash the filter residue with acetone until it turns white, concentrate the filtrate by rotary evaporation, add dropwise to 400mL petroleum ether, place in the lower layer of a refrigerator for cooling and crystallization, filter, dry the solid to obtain yellow flaky crystals, recrystallize the flaky crystals in 600mL hot ethanol (70℃), filter, and dry in a vacuum oven to obtain 24.0g bromoazobenzene, with a yield of 60%, and its chemical structure is shown below:
[0079]
[0080] Weigh 93.3 mmol of KHCO 3 , 96.2mmol of acrylic acid and 100mL of DMF were added to a 1000mL three-necked flask, stirred for 5min, and then 24mmol of bromoazobenzene, 0.27mmol of hydroquinone and 500mL of DMF were added. After stirring evenly, the mixture was heated and refluxed in an oil bath at 100°C for 24h. After the reaction, the reaction solution was cooled and added dropwise to a 1L beaker with a pre-set magnetic and 400mL of deionized water. A yellow powdery precipitate was obtained. After suction filtration, the residue was dried in a vacuum oven at 30°C. The dried solid was dissolved in 300mL of DCM, washed with 5% NaOH aqueous solution and deionized water in turn, anhydrous magnesium sulfate was added to the organic phase overnight, the filtrate was collected by suction filtration, concentrated by rotary evaporation, and dried to obtain a solid; the solid was recrystallized with hot ethanol, the residue was collected by suction filtration, and dried in a vacuum oven at 30°C to obtain 8.3g of yellow powdery crystals, i.e., azobenzene methyl acrylate monomer, referred to as AzoMA. Its H NMR spectrum is Figure 2 shown.
[0081] Example 1
[0082] This embodiment provides a method for preparing a multi-stage assembly material, comprising:
[0083] S1, 2.56 mmol of monomer AzoMA, 0.053 mmol of AIBN, 0.016 mmol of PEG 45 -DMA chain transfer agent and 1.3mL THF solution were added to the reaction tube, stirred and dissolved evenly, and oxygen in the reaction tube was removed through three cycles of liquid nitrogen freezing-vacuuming-nitrogen passing-thawing, and reacted in a 70℃ oil bath for 24h. The reaction was quenched with liquid nitrogen, the reaction system was heated to dissolve, a small amount of THF was added to the reaction solution, and then the reaction solution was dropped into cold ether for precipitation three times to obtain a solid powder, which was dried to obtain an orange-yellow azobenzene block polymer, recorded as PEG 45 -b-PAzoMA 180 , its molecular weight is 34700. Its nuclear magnetic resonance hydrogen spectrum is as follows Figure 3 shown.
[0084] S2, take 5 mg of PEG 45 -b-PAzoMA 180 Add into a single-necked flask containing 250 ml of anhydrous ethanol, ultrasonically disperse for 15 minutes, heat the single-necked flask to 85°C in an oil bath and keep warm for 2 hours; then naturally cool to 15°C in the oil bath to obtain a dispersion of a multi-stage assembly material, which is recorded as BCP-1.
[0085] Example 2
[0086] This embodiment provides a method for preparing a multi-stage assembly material, comprising:
[0087] S1, the same as in Example 1;
[0088] S2, take 5 mg of PEG 45 -b-PAzoMA 180 Add into a single-necked flask containing 250 ml of anhydrous ethanol, ultrasonically disperse for 15 minutes, heat the single-necked flask to 85°C in an oil bath for 2 hours, and then cool it to 15°C within 10 minutes to obtain a dispersion of a multi-stage assembly material, which is recorded as BCP-2.
[0089] Example 3
[0090] This embodiment provides a method for preparing a multi-stage assembly material, comprising:
[0091] S1, the same as in Example 1;
[0092] S2, take 5 mg of PEG 45 -b-PAzoMA 180 Add into a single-necked flask containing 250 ml of anhydrous ethanol, ultrasonically disperse for 15 minutes, heat the single-necked flask to 85°C in an oil bath for 2 hours, and then cool it to 15°C at a rate of 0.2°C / min to obtain a dispersion of a multi-stage assembly material, which is recorded as BCP-3.
[0093] Example 4
[0094] This embodiment provides a method for preparing a multi-stage assembly material, comprising:
[0095] S1, 2.56 mmol of monomer AzoMA, 0.053 mmol of AIBN, 0.016 mmol of PEG 45 -DMA chain transfer agent and 1.3mL THF solution were added to the reaction tube, stirred and dissolved evenly, and oxygen in the reaction tube was removed through three cycles of liquid nitrogen freezing-vacuuming-nitrogen passing-thawing, and reacted in a 70℃ oil bath for 20h. The reaction was quenched with liquid nitrogen, the reaction system was heated to dissolve, a small amount of THF was added to the reaction solution, and then the reaction solution was dropped into cold ether for precipitation three times to obtain a solid powder, which was dried to obtain an orange-yellow azobenzene block polymer, recorded as PEG 45 -b-PAzoMA 123 ; The molecular weight was tested to be 25300.
[0096] S2, take 5 mg of PEG45 -b-PAzoMA 123 Add into a single-necked flask containing 250 ml of anhydrous ethanol, ultrasonically disperse for 15 minutes, heat the single-necked flask to 85°C in an oil bath for 2 hours, and then naturally cool to 15°C in the oil bath to obtain a dispersion of a multi-stage assembly material, which is recorded as BCP-4.
[0097] Example 5
[0098] This embodiment provides a method for strengthening and toughening a resin matrix, comprising:
[0099] 1 g of polyvinyl alcohol was dissolved in 1.5 mL of deionized water to obtain a polyvinyl alcohol solution, and 3 portions were prepared in total; a dispersion of BCP-1 with a mass of 0.5 wt%, 1 wt% and 2 wt% of polyvinyl alcohol and a volume of 10 mL was added to the polyvinyl alcohol solution, and the mixture was stirred at a speed of 200 r / min for 1 hour, and the mixture was added to a polytetrafluoroethylene mold and allowed to stand for 5 hours, and then transferred to 35°C and kept warm for 24 hours to obtain 3 polyvinyl alcohol composite films with different BCP-1 contents, which were recorded as PVA / BCP-1.
[0100] Example 6
[0101] The difference between Example 6 and Example 5 is that the dispersion of BCP-1 is replaced by the dispersion of BCP-2, and the rest is the same as Example 5. The polyvinyl alcohol composite film prepared in Example 6 is recorded as PVA / BCP-2.
[0102] Example 7
[0103] The difference between Example 7 and Example 5 is that the dispersion of BCP-1 is replaced by the dispersion of BCP-3, and the rest is the same as Example 5. The polyvinyl alcohol composite film prepared in Example 7 is recorded as PVA / BCP-3.
[0104] Example 8
[0105] The difference between Example 8 and Example 5 is that the dispersion of BCP-1 is replaced by the dispersion of BCP-4, and the rest is the same as Example 5. The polyvinyl alcohol composite film prepared in Example 8 is recorded as PVA / BCP-4.
[0106] Comparative Example
[0107] 1g of polyvinyl alcohol was dissolved in 1.5mL of deionized water to obtain a polyvinyl alcohol solution, and then 10ml of anhydrous ethanol was added thereto, and the mixture was stirred and mixed at a speed of 200r / min for 1 hour. The mixture was added to a polytetrafluoroethylene mold and allowed to stand for 5 hours, and then transferred to 35°C and kept warm for 24 hours to obtain a polyvinyl alcohol composite film, which was recorded as PVA.
[0108] The microscopic morphologies of the multi-level assembly materials BCP-1, BCP-2, BCP-3 and BCP-4 prepared in Examples 1-4 were studied by transmission electron microscopy. The TEM images are shown in FIG. Figure 4 and Figure 5 shown.
[0109] Figure 4 Azobenzene block polymer PEG 45 -b-PAzoMA 180 TEM images of the prepared multi-level assembly materials BCP-1, BCP-2 and BCP-3, wherein the morphology schematic diagram of BCP-1 is shown in (a), and the TEM images of BCP-1 are shown in (d) and (g); the morphology schematic diagram of BCP-2 is shown in (b), and the TEM images of BCP-2 are shown in (e) and (h); the morphology schematic diagram of BCP-3 is shown in (c), and the TEM images of BCP-3 are shown in (f) and (i). Figure 5 (a) and (b) are azobenzene block polymers PEG 45 -b-PAzoMA 123 TEM image of the prepared multi-level assembly material BCP-4.
[0110] Depend on Figure 4 It can be seen that the multi-level assembly material BCP-1 obtained by natural cooling has a multi-layer blade morphology, the multi-level assembly material BCP-2 obtained by rapid cooling has a single-layer blade morphology, and the multi-level assembly material BCP-3 obtained by slow cooling has a multi-layer square sheet morphology. Figure 5 It can be seen that the multi-level assembly material BCP-4 obtained by natural cooling is a single-layer square sheet morphology. The present application can achieve the regulation of the morphology of the polymer assembly through different processes to form multi-level assemblies such as multi-layer blades, single-layer blades, multi-layer square sheets or single-layer square sheets. Compared with the existing one-dimensional or two-dimensional structure assembly, it has a better strengthening and toughening effect on the resin matrix.
[0111] The multi-stage assembly material in the toughened and reinforced polyvinyl alcohol composite film of Example 5-8 was added to the polyvinyl alcohol composite film at a ratio of 0.5wt%, and the stress-strain curve was tested with the ordinary polyvinyl alcohol composite film of the comparative example. The results are as follows: Figure 6 shown.
[0112] Depend on Figure 6 It can be seen that the toughness and strength of the polyvinyl alcohol composite film containing the assembly are improved to a certain extent compared with the ordinary polyvinyl alcohol film, that is, the addition of the multi-level assembly containing azobenzene liquid crystal polymer realizes the toughening and strengthening of the polyvinyl alcohol resin matrix.
[0113] The mechanical properties of the toughened and reinforced polyvinyl alcohol composite films of Examples 5-8 and the common polyvinyl alcohol composite films prepared in the comparative example were tested. The test results are shown in Table 1.
[0114] Table 1 Mechanical properties test results of different polyvinyl alcohol composite films
[0115]
[0116] From the test results in Table 1, it can be seen that after adding the multi-stage assembly, the tensile toughness of the polyvinyl alcohol composite film is greatly increased. Among them, the blade-shaped assembly has a better toughening effect than the square sheet assembly, such as the toughness increment of PVA / BCP-1 and PVA / BCP-2 is higher than that of PVA / BCP-3 and PVA / BCP-4; the multi-layer assembly has a better toughening effect than the single-layer assembly, such as the toughness increment of PVA / BCP-1 is higher than that of PVA / BCP-2. Among them, the multi-layer blade assembly PVA / BCP-1 has the best toughening effect, which can reach up to 5.2 times that of ordinary polyvinyl alcohol composite film.
[0117] In addition, after adding the multi-stage assembly, the fracture strength, i.e., the fracture strain liquid, of the polyvinyl alcohol composite film increased significantly, and the multi-layer blade assembly PVA / BCP-1 had the best reinforcement effect.
[0118] Although the present application has been described in detail in general terms and in specific embodiments in this specification, it is obvious to those skilled in the art that some modifications or improvements may be made to the present application. Therefore, these modifications or improvements made without departing from the spirit of the present application are within the scope of protection claimed in the present application.
Claims
1. A method for preparing a multi-stage assembly material based on azobenzene liquid crystal block copolymer, characterized in that: include: S1, polymerizing azobenzene methyl acrylate monomer and a chain transfer agent in a first solvent under an inert atmosphere under the action of an initiator to obtain a liquid crystal block copolymer; S2, annealing the liquid crystal block copolymer in a second solvent to obtain a dispersion of a multi-stage assembly material.
2. The preparation method according to claim 1, characterized in that: The chemical structure of the azobenzene methacrylate monomer is shown in formula (I): Wherein, x is an integer of 2 to 12; R1 is selected from any one of methyl, ethyl, propyl, n-butyl, n-pentyl or methoxy.
3. The preparation method according to claim 1, characterized in that: The chemical structure of the chain transfer agent includes any one of the following: Wherein, n is an integer of 20 to 200; m is an integer of 10 to 200.
4. The preparation method according to claim 1, characterized in that: The first solvent includes any one of tetrahydrofuran, dioxane, N,N-dimethylformamide or toluene; The polymerization reaction temperature is 60 to 90° C., and the reaction time is 12 to 72 hours.
5. The preparation method according to claim 1, characterized in that: The second solvent is a poor solvent for the liquid crystal block copolymer or a mixed solvent of a poor solvent for the liquid crystal block copolymer and a good solvent; The poor solvent includes at least one of methanol, ethanol, isopropanol, n-butanol or deionized water; The good solvent includes at least one of N,N-dimethylformamide, dimethyl sulfoxide, tetrahydrofuran, dichloromethane or N-methylpyrrolidone; The volume ratio of good solvent to poor solvent in the mixed solvent is (0.01-0.03):
1.
6. The preparation method according to claim 1, characterized in that: The annealing treatment temperature is 50° C. to 120° C., and the heat preservation time is 0.5 to 24 hours.
7. The preparation method according to claim 1, characterized in that: The molar ratio of the azobenzene methacrylate monomer, the initiator and the chain transfer agent is (30-2000):1:(3-10); The initiator is azobisisobutyronitrile.
8. A multi-stage assembly material prepared by the preparation method according to any one of claims 1 to 7.
9. A method for strengthening and toughening a resin, characterized in that: include: The organic resin matrix solution is mixed evenly with the dispersion of the multi-stage assembly material prepared by the preparation method according to any one of claims 1 to 7, added into a mold and allowed to stand, and then kept warm at 20 to 40° C. for 1 to 30 hours; The mass of the dispersion of the multi-stage assembly material accounts for 0.1-10 wt % of the mass of the organic resin matrix.
10. The method for strengthening and toughening resin according to claim 9, characterized in that: The organic resin matrix solution is prepared by dissolving the organic resin matrix in water, glycerol or ethanol, and the concentration thereof is 0.5 to 3 g / mL; The organic resin matrix is at least one of epoxy resin, polyurethane resin, phenolic resin or polyvinyl alcohol resin.
Citation Information
Patent Citations
Epoxy resin flexibilizer and preparation method thereof
CN115160515A
Cited By
High-temperature-resistant liquid crystal polymer substrate for ultrathin flexible display
CN121432765A
